2018
DOI: 10.1136/jim-2017-000609
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratin-18 and Enhanced Liver Fibrosis Scores in Type 1 and Type 2 Diabetes and Effects of Two Different Insulins

Abstract: Data on cytokeratin-18 (K-18) and enhanced liver fibrosis (ELF) score in insulin-treated diabetes patients with non-alcoholic fatty liver disease (NAFLD) are limited. This study analyzed phase III data comparing basal insulin peglispro (BIL) and insulin glargine in type 1 (T1D), and type 2 diabetes (T2D) (insulin-naïve and insulin-treated). Alanine aminotransferase (ALT), K-18, ELF scores and liver fat content (LFC), measured by MRI, were obtained longitudinally. Baseline K-18 (U/L) was higher in T2D (range: 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, only a few studies investigated the correlations about CK18 in patients infected with HCV [ 10 , 11 ], and limited data confirmed the strong relationship between serum CK18 and HCV-related fibrosis. Sanyal et al [ 10 ] also found CK18 associated with insulins in CHC complicated with T2DM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only a few studies investigated the correlations about CK18 in patients infected with HCV [ 10 , 11 ], and limited data confirmed the strong relationship between serum CK18 and HCV-related fibrosis. Sanyal et al [ 10 ] also found CK18 associated with insulins in CHC complicated with T2DM.…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies investigated the correlations about CK18 in patients infected with HCV [ 10 , 11 ], and limited data confirmed the strong relationship between serum CK18 and HCV-related fibrosis. Sanyal et al [ 10 ] also found CK18 associated with insulins in CHC complicated with T2DM. Additionally, there have been many developed noninvasive serum biomarkers for predicting liver fibrosis in CHC patients without any other metabolic diseases [ 12 ], but no marker was specially developed for CHC-T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another insulin analogue, peglispro [28,29,30,31] was derived by covalent attachment of a linear 20 kD polyethylene polymer to the LysB28 side chain in insulin lispro.…”
mentioning
confidence: 99%